Aerosol Jet Printing of a Benzocyclobutene‐Based Ink as Adhesive Material for Wafer Bonding Application. Issue 5 (4th December 2022) - Iervolino, Filippo; Baldini, Angelica; Gelmi, Ilaria; Castoldi, Laura; Suriano, Raffaella; Levi, Marinella
Abstract: Aerosol jet printing (AJP) is an emerging additive manufacturing technology that is gaining increasing attention in the electronic field. Several studies have been carried out on the AJP of conductive, semiconductive, and dielectric polymers for electronic applications. However, wafer bonding is an application that is still uncovered by literature. Therefore, in this work, the AJP of benzocyclobutene (BCB) as a polymeric adhesive for wafer bonding is presented for the first time. A thorough characterization of the processing parameters is carried out to identify the most ideal conditions for printing at a relatively high speed. Then, square patterns are printed, proving the versatility of the AJP technology in terms of the reachable thickness of the deposited BCB patterns. Complex patterns with a resolution of ≈60 µm are also printed. The bonding properties of the BCB are characterized from a morphological and mechanical point of view. In particular, the shear strength of the BCB coatings deposited with AJP is ≈39 MPa and it is comparable with the shear strength of BCB coating deposited by spin‐coating. Consequently, AJP represents a valid alternative for the deposition of polymeric adhesive for wafer bonding. Abstract : Aerosol jet printing is an additive manufacturing technology able to deposit polymeric adhesives such as benzocyclobutene for wafer bonding applications. It is possible to print simple and complex shapes. The bonding strength of the material deposited with aerosol jet printing is comparable with the one obtained using more traditional deposition techniques.